2012
DOI: 10.1016/j.mri.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cortical lesions in multiple sclerosis at 7 T using white matter signal attenuation

Abstract: Cortical lesions have recently been a focus of multiple sclerosis (MS) MR research. In this study, we present a white matter signal attenuating sequence optimized for cortical lesion detection at 7 T. The feasibility of white matter attenuation (WHAT) for cortical lesion detection was determined by scanning eight patients (four relapsing/remitting MS, four secondary progressive MS) at 7 T. WHAT showed excellent gray matter–white matter contrast, and cortical lesions were hyperintense to the surrounding cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…One of these studies by using T2*-weighted gradient-echo images even suggested that this sequence should be the new criterion standard for the detection of cortical lesions in patients with MS. 33 Another recent study reported that white matter signal attenuation at 7T is feasible and is able to detect cortical abnormalities at 7T. 35 To our knowledge, the value of the recommended sequences for clinical use at 7T has not yet been investigated nor has the use of DIR. Our results show that the highest total cortical lesion detection at 7T is gained with 3D-FLAIR.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies by using T2*-weighted gradient-echo images even suggested that this sequence should be the new criterion standard for the detection of cortical lesions in patients with MS. 33 Another recent study reported that white matter signal attenuation at 7T is feasible and is able to detect cortical abnormalities at 7T. 35 To our knowledge, the value of the recommended sequences for clinical use at 7T has not yet been investigated nor has the use of DIR. Our results show that the highest total cortical lesion detection at 7T is gained with 3D-FLAIR.…”
Section: Discussionmentioning
confidence: 99%
“…Bluestein et al [24] implemented a white matter signal attenuating sequence (WHAT) at 7T, by optimizing the gray matter-white matter and gray matter-cortical lesion contrast. Mainly mixed lesions were detected well, whereas the detection of subpial lesions proved to be more difficult.…”
Section: Sethi Et Al [22mentioning
confidence: 99%
“…The inversion time is usually set to null or significantly attenuate cerebrospinal fluid (CSF) signal, which results in good white matter (WM) ‐ gray matter (GM) contrast. This sequence is routinely used in volumetric analysis, WM‐GM segmentation, epilepsy imaging as well as in the detection and characterization of lesions from multiple sclerosis (MS) and other WM degenerative diseases . We refer to this sequence, henceforth, as CSF‐nulled (CSFn) MP‐RAGE or conventional MP‐RAGE.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this sequence, henceforth, as CSF‐nulled (CSFn) MP‐RAGE or conventional MP‐RAGE. A variant of the MP‐RAGE method was recently reported by Bluestein et al at 7 Tesla (T) , where WM signal rather than CSF signal was nulled for better visualization of cortical MS lesions at 7T. We refer to this variant sequence as WM‐nulled (WMn) MP‐RAGE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation